Carotenoid production by Rhodotorula rubra cultivated in sugarcane juice, molasses, and syrup Produção de carotenoides por Rhodotorula rubra cultivada em caldo, melaço e xarope de cana-de-açúcar - David Banzatto (Food Science and Technology, 2013)
The Rhodotorularubra biomass and carotenoids production was evaluated in sugarcane juice, molasses, and syrup based media. The effects of media supplementation with urea- nitrogen or the commercial nutrient called Nitrofos KL was also verified. The experimental design used was a completely randomized factorial with 3 substrates (juice, molasses, and syrup) and three supplementations (control, urea, and Nitrofos KL). The results were submitted to variance analysis and Tukey test at 5% probability. The highest production of yeast dry mass was obtained with molasses media supplemented with urea or Nitrofos KL (15.09 and 14.87 g/L respectively). The intracellular carotenoid production was high in the media without supplementation (0.329 mg/g). The best growth medium for the volumetric production was molasses (2.74 mg/L), while those supplemented with urea and Nitrofos KL produced 2.55 and 2.32 mg/L, respectively. The major carotenoids produced were torulene, torularhodin, and β-carotene. The lowest carbohydrate consumption was observed in the sugarcane juice medium without supplementation, while the highest consumption was observed in the urea based supplementation medium. A produção de biomassa e de carotenoides por Rhodotorula rubra foi estudada em meios à base de caldo, melaço e xarope de cana. Avaliou-se o efeito da suplementação dos meios com nitrogênio na forma de ureia ou do nutriente comercial Nitrofos KL. O delineamento experimental utilizado foi o inteiramente casualizado, no esquema fatorial 3 × 3, sendo um dos fatores o substrato (caldo, melaço e xarope) e o outro a suplementação (controle, ureia e Nitrofos KL). Os resultados foram submetidos à análise de variância e teste de Tukey a 5% de probabilidade. As maiores produções de massa seca de levedura foram obtidas no meio à base de melaço suplementado com ureia ou Nitrofos KL (15,09 e 14,87 g/L, respectivamente). A produção de carotenoides intracelular foi elevada em todos os meios estudados sem suplementação (0,329 mg/g). Para a produção volumétrica, o melhor meio foi o melaço (2,74 mg/L), enquanto a suplementação com ureia e com Nitrofos KL produziu 2,55 e 2,32 mg/L, respectivamente. Os principais carotenoides produzidos foram toruleno, torularrodina e β-caroteno. No meio à base de caldo de cana sem suplementação, houve o menor consumo de carboidratos, enquanto que o meio com suplementação à base de ureia obteve o maior consumo.